DAMPAK COVID 19 TERHADAP PENDAPATAN KIOS PERTANIAN DI KECAMATAN DURENAN KABUPATEN TRENGGALEK - Dewi Oryza Sativa, Rima; Zamrodah, Yuhanin; Wahyu Budiman, Eko; Aditya Prayudhi, Luhur (Universitas Islam Balitar, 2023)
Agriculture is one of the sectors impacted by the Covid 19 pandemic. The Trenggalek area as an agricultural production area is also affected by this. The decline in people's purchasing power towards agricultural production is the cause. This has an impact on the agricultural kiosk business. As a provider of agricultural needs and equipment, the agricultural kiosk business was also affected. Based on problem identification, this study aims to determine (1) the effect of the Covid 19 pandemic on income at agricultural kiosks (2) a comparison of profit ratios from agricultural kiosks before, during and after the Covid 19 pandemic. Based on the results of this study, namely by comparing the value of the R/C ratio of the farming business from the agricultural kiosk before, during and after the pandemic slumped, information can be obtained on the impact of the pandemic on the agricultural kiosk business. Based on the value of the R/C ratio, it has decreased, namely 1.33 before the pandemic became 1.26 during the pandemic, and has increased again to 1.32 after the pandemic subsided. This decrease was caused by a decrease in the purchasing power of farmers towards the decreased needs and agricultural equipment. However, this decrease was not significant because the R/C ratio during the pandemic was still > 1, so it was still feasible to work on. The agricultural sector is a potential sector that can be developed after the Covid pandemic. Moreover, the Trenggalek area is currently experiencing an increase in the level of agricultural production. The agricultural kiosk business will be a viable business to be developed in the future in accordance with the development of the agricultural sector.